Design, synthesis and biological evaluation of antiparasitic dinitroaniline-ether phospholipid hybrids - Roussaki, Marina; Magoulas, George E.; Fotopoulou, Theano; Santarem, Nuno; Barrias, Emile; Pöhner, Ina; Luelmo, Sara; Afroudakis, Pantelis; Georgikopoulou, Kalliopi; Nevado, Paloma Tejera; Eick, Julia; Bifeld, Eugenia; et al. (Bioorganic chemistry, 2023)
A series of nine novel ether phospholipid-dinitroaniline hybrids were synthesized in an effort to deliver more potent antiparasitic agents with improved safety profile compared to miltefosine. The compounds were evaluated for their in vitro antiparasitic activity against L. infantum, L.donovani, L. amazonensis, L. major and L. tropica promastigotes, L. infantum and L. donovani intracellular amastigotes, Trypanosoma brucei brucei and against different developmental stages of Trypanosoma cruzi. The nature of the oligomethylene spacer between the dinitroaniline moiety and the phosphate group, the length of the side chain substituent on the dinitroaniline and the choline or homocholine head group were found to affect both the activity and toxicity of the hybrids. The early ADMET profile of the derivatives did not reveal major liabilities. Hybrid 3, bearing an 11-carbon oligomethylene spacer, a butyl side chain and a choline head group, was the most potent analogue of the series. It exhibited a broad spectrum antiparasitic profile against the promastigotes of New and Old World Leishmania spp., against intracellular amastigotes of two L. infantum strains and L. donovani, against T. brucei and against T. cruzi Y strain epimastigotes, intracellular amastigotes and trypomastigotes. The early toxicity studies revealed that hybrid 3 showed a safe toxicological profile while its cytotoxicity concentration (CC50) against THP-1 macrophages being >100 μM. Computational analysis of binding sites and docking indicated that the interaction of hybrid 3 with trypanosomatid α-tubulin may contribute to its mechanism of action. Furthermore, compound 3 was found to interfere with the cell cycle in T. cruzi epimastigotes, while ultrastructural studies using SEM and TEM in T. cruzi showed that compound 3 affects cellular processes that result in changes in the Golgi complex, the mitochondria and the parasite’s plasma membrane. The snapshot pharmacokinetic studies showed low levels of 3 after 24 h following oral administration of 100 mg/Kg, while, its homocholine congener compound 9 presented a better pharmacokinetic profile.